Unlocking the irrigation potential in sub-Saharan Africa: are public-private partnerships the way forward? - Waltina Scheumann; Annabelle Houdret; Michael Brüntrup (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
Irrigation can help to improve and stabilise agricultural productivity, thereby contributing to food security and to resilience against climate change. Irrigation – either full or supplementary – reduces reliance on erratic rainfall/droughts and increases yields; it extends cropping periods and cycles, allows the cultivation of a broader spectrum of crops, and provides stable conditions for applying further yield-increasing means (fertilizers). Irrigation also encourages farmers to invest, on the one hand, and financial institutions to provide credits, on the other. Moreover, there is evidence from Asia that irrigation has the potential to reduce both poverty rates and income inequalities. Several sub-Saharan African (SSA) countries still have a significant potential for expanding the area under irrigation. While small-scale irrigation can be managed by individual farmers or farmer groups (though with some difficulties and risks), for larger schemes ? which tap larger potentials ? this is hardly an option: public financial sources are constrained, and public management of irrigation schemes has shown many disadvantages. This Briefing Paper argues that, instead, public-private-partnership (PPP) projects in irrigation can be beneficial for smallholders, rural communities, investors and the public if certain conditions are met. The challenges to realising inclusive PPPs are the following: Due to the “public good” character of water, the “common pool resources” character of irrigation schemes, and SSA land tenure systems, governments must play a pro-active role in creating security and stability for investments in relation to land- and water-use rights and in protecting public goods. Investing in water infrastructure alone is not sufficient in SSA countries. It must be embedded in a comprehensive support package including access to extension services and financial products, input supply, and ? above all ? access to stable markets. All successful PPPs we reviewed in SSA have in common that smallholders have established farmer-owned liability companies to run commercial businesses. These companies have entered into contracts with private sector companies for irrigation management, service provision and market access. Farmers are represented on the management boards of their companies. For such arrangements, smallholders need long-term support such as vocational training along with assistance in designing contracts and acquiring management skills. PPP arrangements require country- and site-specific solutions and must address the risks of the various parties involved if it is to be ensured that PPPs are development-friendly, are economically viable and protect natural resources.
Keywords: 330; Strukturwandel; wirtschaftliche Entwicklung und Beschäftigung; Landwirtschaft und ländliche Entwicklung